Greenland Mass Trends From Airborne and Satellite Altimetry During 2011–2020. Issue 4 (28th March 2022) - Khan, Shfaqat A.; Bamber, Jonathan L.; Rignot, Eric; Helm, Veit; Aschwanden, Andy; Holland, David M.; van den Broeke, Michiel; King, Michalea; Noël, Brice; Truffer, Martin; Humbert, Angelika; Colgan, William; et al.
Abstract: We use satellite and airborne altimetry to estimate annual mass changes of the Greenland Ice Sheet. We estimate ice loss corresponding to a sea‐level rise of 6.9 ± 0.4 mm from April 2011 to April 2020, with a highest annual ice loss rate of 1.4 mm/yr sea‐level equivalent from April 2019 to April 2020. On a regional scale, our annual mass loss timeseries reveals 10–15 m/yr dynamic thickening at the terminus of Jakobshavn Isbræ from April 2016 to April 2018, followed by a return to dynamic thinning. We observe contrasting patterns of mass loss acceleration in different basins across the ice sheet and suggest that these spatiotemporal trends could be useful for calibrating and validating prognostic ice sheet models. In addition to resolving the spatial and temporal fingerprint of Greenland's recent ice loss, these mass loss grids are key for partitioning contemporary elastic vertical land motion from longer‐term glacial isostatic adjustment (GIA) trends at GPS stations around the ice sheet. Our ice‐loss product results in a significantly different GIA interpretation from a previous ice‐loss product. Plain Language Summary: Greenland ice loss has accelerated over the last three decades. The Greenland Ice Sheet is currently one of the largest contributors to global sea‐level rise. We combine airborne and satellite altimetry measurements to make annual digital elevation models of the ice sheet during 2011–2020. Over this period, we find that the ice sheet lost an ice volume corresponding to 6.9 ± 0.4 mm of global sea‐level equivalent. The peak loss year was April 2019 to April 2020, when the ice sheet lost 1.4 mm of global sea‐level equivalent. This peak loss rate is equivalent to losing 15, 850 tonnes of ice per second for 12 months. We also find that the acceleration of ice loss differs across different ice‐sheet sectors. We suggest that these regional ice loss trends may be a good target for the ice‐sheet models used to project future ice loss. Key Points: The Greenland Ice Sheet contributed 6.9 ± 0.4 mm to sea‐level from April 2011 to April 2020 Satellite altimetry suggests a peak annual ice loss of 498 ± 45 Gt from April 2019 to April 2020 The terminus of Jakobshavn Isbræ is once again dynamically thinning, following a period of dynamic thickening during 2016–2018